Dynamic Changes of Tumor-infiltrating Immune Cells in Mice with MC38 Colon Cancer - ZHANG Boyang; CHEN Huanpeng; YU Wenlan; LIU Zhonghua; HUANG Chaofeng (Shiyan dongwu yu bijiao yixue, 2021)
ObjectiveTo observe the dynamic changes of tumor-infiltrating immune cells in tumor-bearing mice during tumor development.MethodsMouse colon cancer MC38 cells were transplanted subcutaneously into 24 C57BL/6J mice, and the changes in body mass and tumor size of mice were recorded once a week after tumor-bearing, The levels of tumor-infiltrating immune cells, including CD45+ T cells, CD3+ T cells, CD8+ T cells, CD4+ T cells, natural killer (NK) cells, dendritic cells, macrophages, M1-type macrophages, M2-type macrophages, myeloid-derived suppressor cells (MDSCs), mononuclear-like MDSCs (M-MDSCs), and granulocytic MDSCs (G-MDSCs) were detected by flow cytometry once a week for 4 weeks.ResultsAs the colon cancer tumor of the mouse grows, total CD45+ T cellular level decreased, and CD8+ T cellular level steadily decreased to an irreversible level, but CD4+ T cells proportion rapidly increased at the early stage of the tumor-bearing, quantity of infiltrating cells in the unit volume increased by 8 times, and T cells of tumor-infiltration almost were CD4+ phenotype. The nonspecific immune response level represented by NK cells continued to decline, but the dendritic cells continued to accumulate in the tumor. The immunosuppressive action was further enhanced through the activation of arginase-1 (ARG1) and inducible nitric oxide synthetase (iNOS). Macrophage infiltration levels showed no significant change, but the gliding speed for the quantity of infiltrating type-Ⅰ macrophages was obviously higher than that of type-Ⅱ macrophages. The proportion of MDSCs per unit volume showed no decreasing trend, and the cells continued to accumulate in the tumor. G-MDSC infiltration level showed a steady decrease, while M-MDSC infiltration level showed an increasing trend, the proportion of M-MDSCs were higher than that of G-MDSCs.ConclusionAfter transplanting MC38 colon cancer cells in mice, the level of immune cell infiltration in the tumor tissue declined, tumor immunology gradually became dominat, thus promoting the development of colon cancer. The Th1/Th2 drift occurred in the tumor. Specific and nonspecific immune response levels were significantly decreased on an average, and the infiltrating monocytes and granulocytes were mainly Ly6C+. Tumor-associated dendritic cells and macrophages play an important immunosuppressive role. CD4+T cells and M-MDSCs might be the key for promoting tumor immunity.